Identification of the contextual factors influencing the successful implementation of in-service training policies for the health workforce in Iran - Azam Choopani; Jalal Arabloo; Seyed Hasan Arkian; Soudabeh Vatankhah (BMC Medical Education)
Abstract Background In-service training is critical for achieving organizational goals and developing the health workforce. Therefore, this study aimed to identify contextual factors that significantly impact the implementation of in-service training policies for the health workers. Methods This study employed an inductive qualitative approach, utilizing semi-structured interviews as the data collection method. The target group consisted of human resources managers and experts. Purposeful sampling was conducted using the snowball method. A total of 23 interviews were conducted, and data saturation was achieved. Framework analysis was performed using MAXQDA10 software to analyze the data. To enhance the credibility of the findings, interview transcripts, and the initially extracted codes were shared with participants for verification. Additionally, various methods were employed to ensure the accuracy and reliability of the data, including seeking input and additional comments from two colleagues and one expert familiar with qualitative research, as well as sending the interview transcripts and extracted codes to each participant for correction during the data collection phase. Results The analysis of the data identified seven themes and 16 subthemes related to the implementation of in-service training for healthcare workers. These themes include social factors, personal characteristics, economic and political factors, crises and epidemics, organizational factors, and legal factors. Social factors, such as social crises and demographic characteristics, can affect the type of training provided. Personal characteristics, including motivation, age, job position, and gender, can influence the implementation of training. Political and economic factors, such as government policies and budget constraints, also play a role. Crises and epidemics present opportunities for relevant training. Organizational factors, such as top management commitment and organizational culture, determine the success of training. Legal factors, including restrictive laws and incentives, impact the implementation of training. Conclusions The implementation of policies cannot be considered in isolation from contextual factors. Therefore, decision-makers and policymakers should thoroughly identify and analyze the relevant contextual factors when formulating and implementing policies. This approach will enable them to make informed decisions based on the specific context.